PENGARUH KINERJA LOGISTIK TERHADAP KINERJA OPERASIONAL PADA UKM ROTAN DI KOTA PALU - Ardiansyah, Ardiansyah (Fakultas Ekonomi Universitas Tadulako, 2015)
The aim of this research is to describe the influence of logistic performance on operational performance in the rattan small-medium business in Palu. Population of this research is 24 Rattan small-medium business, which consists of 24 business owners as respondents, and 24 active employees. In total, the sample of this research is 48 people who selected with census method. Method of analysis is multiple linear regressions by using software of SPSS for Windows Release 16.0. Hypothesis test shows significance level of ? = 0.05 and reliability test using the coefficient values shows cronbach alpha with coefficient of ? = 0,60. The result indicates that logistic performance simultaneously have significant influence on operational performance, with adjusted R-square value of 46.4%. Partially, with the standard of ? = 0.05, X1, X2 and X3 have significant influence on Y with sig. value of 0.033, 0.037 and 0.000 respectively. The correlation test shows a correlation coefficient by 0.706, which means that the variable of logistic performance has a strong relationship with the operational performance of 70.6%.